2023
DOI: 10.1177/1420326x231158512
|View full text |Cite
|
Sign up to set email alerts
|

Passive building design for improving indoor thermal comfort in tropical climates: A bibliometric analysis using CiteSpace

Abstract: This paper reviews the literature on passive building design for improving indoor thermal comfort in tropical climates through a bibliometric analysis. The Web of Science database and CiteSpace were searched, and 722 articles were selected and analyzed to form the body of this article. An overview of the evolution of publications from 1984 to 2021 is first presented, followed by an examination of the co-citation networks of journals, countries, keywords, documents and authors. Co-occurrence analysis of 391 key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…However, concerns still persist regarding the energy consumption of residential buildings in general, and difficulties remain in articulating a precise definition of sustainability in this context. Although previous studies have employed bibliometric methods to examine specific aspects of residential design evaluation, such as satisfaction assessment [84], passive housing design evaluation [85], building life-cycle assessment [86], evaluation of smart housing for older adults [87], and solar technology for residential buildings [88,89], there remains a lack of comprehensive discussion on residential design evaluation as a whole. While evaluating specific aspects of residential design is crucial for ensuring housing quality, the focus of this study lies in observing and discussing the overall trends and comprehensive development of residential design evaluation, which allows us to track the dynamic changes in residential design.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns still persist regarding the energy consumption of residential buildings in general, and difficulties remain in articulating a precise definition of sustainability in this context. Although previous studies have employed bibliometric methods to examine specific aspects of residential design evaluation, such as satisfaction assessment [84], passive housing design evaluation [85], building life-cycle assessment [86], evaluation of smart housing for older adults [87], and solar technology for residential buildings [88,89], there remains a lack of comprehensive discussion on residential design evaluation as a whole. While evaluating specific aspects of residential design is crucial for ensuring housing quality, the focus of this study lies in observing and discussing the overall trends and comprehensive development of residential design evaluation, which allows us to track the dynamic changes in residential design.…”
Section: Discussionmentioning
confidence: 99%
“…Kolani et al [19] surveyed the research on design of passive buildings for enhancing interior thermal comfort from 1984 to 2021. The findings revealed that real-time field investigations, as opposed to dynamic models, were the most remarkable study on the passive ventilation and thermal comfort of tropical structures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to existing literature, building retrofit measures can be categorized into several key areas, including the building envelope, 7,8 HVAC (Heating, Ventilation and Air Conditioning) systems, 9 equipment upgrades, 10 integration of new techniques such as renewable energies, 11 occupant behaviour, energy management practices 12,13 and regulatory considerations. Selecting the most suitable retrofit measure for existing buildings is a complex undertaking due to the multitude of multidimensional factors that must be taken into account.…”
Section: Introductionmentioning
confidence: 99%